Diagnosis and Clinical Management of Gout Arthritis - Susi Setyawati, Kadek (Jurnal KESANS : Kesehatan dan Sains, 2024)
Gout is an inflammatory joint disease caused by an inflammatory response to monosodium urate (MSU) crystals in the joint fluid, cartilage, bones, tendons, bursas, or other sites. High uric acid levels increase the likelihood of gouty arthritis, but not all high uric acid levels will develop into gout. Gout has a predilection for the lower extremities such as the first MTP, which is the most common site of acute gout known as podagra. The etiology of gout is usually multifactorial, including genetic risk factors, medical comorbidities, and dietary factors. gout has now been recognized as a global health problem and has gained attention due to its increasing incidence rate, multiple metabolic comorbidities, and high premature mortality, so patients with gouty arthritis need to be diagnosed and managed appropriately.